PESTICIDE POISONING INDUCED FATALITIES: TRENDS IN A SEMI-URBAN REGION IN INDIAN SUBCONTINENT (Journal of Forensic Medicine & Toxicology, 2014)
Poisoning unintentional, intentional; suicidal, accidental or homicidal is a perpetual problem with great social impact for any society. India- primarily an agrarian economy where easy availability, lax regulatory control on distribution and sale of pesticides makes them easily accessible. The study conducted at Dept. of Forensic Medicine, Guntur Medical College, Guntur, AP during the period Jan 2007 to Dec 2007 retrospectively analyzed the poisoning cases brought for medico-legal postmortem examination. The victims were predominantly males of the age group 21-30 years with intentional self ingestion of pesticides especially Organophosphorus compounds accounted for the highest number of cases.
Keywords: Poisoning; Suicidal Poisoning; Organophosphorus Compounds; Pesticides